Getting the prices right: Drivers' cruising choices in a serious parking game. (November 2022) - Geva, Sharon; Fulman, Nir; Ben-Elia, Eran
Abstract: Scarcity of on-street parking in city centers is a known factor motivating drivers to drive slowly ("to cruise") while searching for an available parking place and is associated with negative externalities e.g. congestion, accidents, fuel waste, and air pollution. Finding the correct prices is suggested to bring cruising to a sustainable level. Current research methods based on surveys and simulations fail to provide a complete understanding of drivers' cruising preferences and their behavioral response to price changes. We used the PARKGAME serious game, which provides a real-world abstraction of the dynamic cruising experience. Eighty-three players participated in an experiment under two pricing scenarios. Pricing was spatially designed as "price rings" decreasing when receding from the desired destination point. We analyzed search time, parking distance, parking location choice, and spatial searching patterns. We show that such a pricing policy may substantially reduce the cruising problem, motivating drivers to park earlier—further away from the destination or in the lot, especially when occupancy levels are extremely high. We further discuss the policy implications of these findings.